Seasonal variations in gut microbiota of semiprovisioned rhesus macaques (Macaca mulatta) living in a limestone forest of Guangxi, China - Liu, Hongying; Chen, Ting; Li, Yuhui; Zheng, Jingjin; Liu, Zheng; Li, Youbang; Huang, Zhonghao (Frontiers in Microbiology, 2022)
Assessment of gut microbiota, used to explore ecological adaptation strategies and evolutionary potential of species, provides a new viewpoint to the conservation and management of endangered animals. In this research, the gut microbiota of a group of semiprovisioned rhesus macaques (Macaca mulatta) living in a limestone forest exhibiting seasonal changes in plant items were studied to investigate the adaptation strategies of these macaques to this specific habitat. The findings revealed significant seasonal changes in the diversity and composition of the rhesus macaques’ gut microbiota, which were higher in the rainy season than in the dry season. In the rainy season, Bacteroidetes (31.83% ± 16.14% vs. 19.91% ± 18.20%) were significantly increased and Prevotella (23.70% ± 15.33% vs. 15.40% ± 16.10%), UCG-002 (4.48% ± 3.16% vs. 2.18% ± 2.01%), and UCG-005 (4.22% ± 2.90% vs. 2.03% ± 1.82%) were more enriched at the genus level. In the dry season, Firmicutes significantly increased (71.84% ± 19.28% vs. 60.91% ± 16.77%), and Clostridium_sensu_stricto_1 (8.45% ± 9.72% vs. 4.76% ± 6.64%), Enterococcus (10.17% ± 13.47% vs. 0.69% ± 2.36%) and Sarcina (4.72% ± 7.66% vs. 2.45% ± 4.71%) were more enriched at the genus level. These differences in gut microbiota may be due to seasonal variations in plant items in these habitats alongside changes in the provisioned foods from tourists. Additionally, deterministic processes predominate the assembly of the macaque’s gut microbiota community. This indicates that the animal’s high reliance on natural plants and provisioned foods increased the impact of deterministic processes. This study concludes that a balance between provisioned foods and natural plants might be vital in shaping the gut microbiota in the macaques. Furthermore, the dynamic adjustment in gut microbiota might be a physiological mechanism for the macaques in response to the seasonal variations in the ecological factors and food provision.